Assisted reproductive technologies do not alter mutation frequency or spectrum - Caperton, Lee (National Academy of Sciences, 2007)
Assisted reproductive technologies (ARTs) have now contributed to the birth of >3 million babies worldwide, but concerns remain regarding the safety of these methods. We have used a transgenic mouse model to examine the effects of ARTs on the frequency and spectrum of point mutations in midgestation mouse fetuses produced by either natural reproduction or various methods of ART, including preimplantation culture, embryo transfer, in vitro fertilization, intracytoplasmic sperm injection, and round spermatid injection. Our results show that there is no significant difference in the frequency or spectrum of de novo point mutations found in naturally conceived fetuses and fetuses produced by in vitro fertilization, intracytoplasmic sperm injection, or round spermatid injection. These results, based on analyses of a transgenic mouse system, indicate that with respect to maintenance of genetic integrity, ARTs appear to be safe.